The brahmin left, the merchant right and the bloc bourgeois. Issue 4 (4th July 2022) - Amable, Bruno; Darcillon, Thibault
Abstract: In a recent paper, Piketty argues that the vote for the left in France, the UK and the USA tends increasingly to be associated with a high education level whereas a traditional class- or income-based divide separated left from right individuals in the 1950s and 1960s. The current situation would be characterised by a dominance of ' elites' in left and right constituencies: financially rich elites vote for the right (merchant right), high-education elites vote for the left (brahmin left). Using ISSP data for 17 countries, this paper tests the influence of income and education inequalities on political leaning and a variety of policy preferences: the support for redistribution, for investment in public education, for globalisation and immigration. Results show that income levels are still relevant for the left-right divide, but the influence differs across education levels. Our findings also point to a certain convergence of opinion among the Brahmin left and the merchant right, which could lead to a new political divide beyond the left and the right, uniting a bloc bourgeois .